A myosin motor that selects bundled actin for motility - Nagy, Stanislav (National Academy of Sciences, 2008)
Eukaryotic cells organize their contents through trafficking along cytoskeletal filaments. The leading edge of a typical metazoan cytoskeleton consists of a dense and complex arrangement of cortical actin. A dendritic mesh is found across the broad lamellopodium, with long parallel bundles at microspikes and filopodia. It is currently unclear whether and how myosin motors identify the few actin filaments that lead to the correct destination, when presented with many similar alternatives within the cortex. Here we show that myosin X, an actin-based motor that concentrates at the distal tips of filopodia, selects the fascin-actin bundle at the filopodial core for motility. Myosin X moves individual actin filaments poorly in vitro, often supercoiling actin into plectonemes. However, single myosin X motors move robustly and processively along fascin-actin bundles. This selection requires only parallel, closely spaced filaments, as myosin X is also processive on artificial actin bundles formed by molecular crowding. Myosin X filopodial localization is perturbed in fascin-depleted HeLa cells, demonstrating that fascin bundles also direct motility in vivo. Our results demonstrate that myosin X recognizes the local structural arrangement of filaments in long bundles, providing a mechanism for sorting cargo to distant target sites.